Routes to Control of H2 Coulomb Explosion in Few-Cycle Laser Pulses - Alnaser, A. S.; Tong, X. M.; Osipov, T.; Voss, S.; Maharjan, C. M.; Ranitovic, P.; Ulrich, B.; Shan, B.; Chang, Z.; Lin, C. D.; Cocke, C. L. (My University, 2004)
We have measured coincident ion pairs produced in the Coulomb explosion of H2 by 8–30 fs laser pulses at different laser intensities. We show how the Coulomb explosion of H2 can be experimentally controlled by tuning the appropriate pulse duration and laser intensity. For laser pulses less than 15 fs, we found that the rescattering-induced Coulomb explosion is dominated by first-return recollisions, while for longer pulses and at the proper laser intensity, the third return can be made to be the major one. Additionally, by choosing suitable pulse duration and laser intensity, we show H2 Coulomb explosion proceeding through three distinct processes that are simultaneously observable, each exhibiting different characteristics and revealing distinctive time information about the H2 evolution in the laser pulse.